Individual Differences in How Desirable People Think They Are as a Mate - Fernandez-Tapia, A (Springer, 2023)
Mate value is an important concept in mate choice research although its operationalization and understanding are limited. Here, we reviewed and evaluated previously established conceptual and methodological approaches measuring mate value and presented original research using individual differences in how people view themselves as a face-valid proxy for mate value in long- and short-term contexts. In data from 41 nations (N = 3895, M age = 24.71, 63% women, 47% single), we tested sex, age, and relationship status effects on self-perceived mate desirability, along with individual differences in the Dark Triad traits, life history strategies, peer-based comparison of desirability, and self-reported mating success. Both sexes indicated more short-term than long-term mate desirability; however, men reported more long-term mate desirability than women, whereas women reported more short-term mate desirability than men. Further, individuals who were in a committed relationship felt more desirable than those who were not. Concerning the cross-sectional stability of mate desirability across the lifespan, in men, short- and long-term desirability rose to the age of 40 and 50, respectively, and decreased afterward. In women, short-term desirability rose to the age of 38 and decreased afterward, whereas long-term desirability remained stable over time. Our results suggest that measuring long- and short-term self-perceived mate desirability reveals predictable correlates. © 2023, The Author(s).
Keywords: Mate value; Mate desirability; Attractiveness; Dark Triad; Sex differences; Mating